An Assessment of Incorporating Online Learning in Higher Education - David Fincham (Modern Perspectives in Language, Literature and Education Vol. 5, 2021)
Learning and teaching have traditionally been viewed as a direct interpersonal classroom activity in educational settings. New forms of teaching and evaluation have emerged as a result of technological advancements, and they have gradually become a more prevalent aspect in education. With the advancement of information technology in general, and the Internet and online technologies in particular, there has been a growing emphasis on the development of distance learning methods, which allows students to expand their learning beyond the constraints of space and time. The purpose of this paper is to present the findings of a case-study investigation into student perceptions of the addition of an e-learning component as part of their experience of an M.A. programme in Catholic School Leadership at St Mary’s University, Twickenham. Students were able to participate in a "virtual classroom" by engaging in online learning, where they were able to share discussions sparked by online questions. As a result, the introduction of online learning represents a significant advancement that has the potential to impact pedagogy and assessment. As a result of this research, the following conclusion can be drawn: While there were some concerns regarding the facility’s implementation, students generally agreed that online activities improved the quality of their education.